Eating and shift work - effects on habits, metabolism and performance - Arne Lowden; Claudia Moreno; Ulf Holmbäck; Maria Lennernäs; Philip Tucker (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
Compared to individuals who work during the day, shift workers are at higher risk of a range of metabolic disorders and diseases (eg, obesity, cardiovascular disease, peptic ulcers, gastrointestinal problems, failure to control blood sugar levels, and metabolic syndrome). At least some of these complaints may be linked to the quality of the diet and irregular timing of eating, however other factors that affect metabolism are likely to play a part, including psychosocial stress, disrupted circadian rhythms, sleep debt, physical inactivity, and insufficient time for rest and revitalization. In this overview, we examine studies on food and nutrition among shift workers [ie, dietary assessment (designs, methods, variables) and the factors that might influence eating habits and metabolic parameters]. The discussion focuses on the quality of existing dietary assessment data, nutritional status parameters (particularly in obesity), the effect of circadian disruptions, and the possible implications for performance at work. We conclude with some dietary guidelines as a basis for managing the nutrition of shift workers.